Trace Determination of Cadmium in Water Matrix by Matrix Matching Calibration Strategy-Based UV-Vis Spectrophotometer After Its Preconcentration - Yagmuroglu, Ozan; Bakirdere, Emine Gulhan; Bakirdere, Sezgin (SPRINGER INT PUBL AG, 2024)
In this study, an analytical method based on UV-Vis spectrophotometer was developed for the determination of trace amounts of cadmium in tap water samples. The analyte in samples to be analyzed was firstly preconcentrated using the liquid-liquid microextraction method. (Z)-4-bromo-2[(naphthalene-2-ylimino)-methyl]phenol was used as a complexing agent in the microextraction process. Parameters affecting the efficiency of the liquid-liquid microextraction (LLME) process applied for preconcentration were optimized before starting the analysis. As a result of the analysis performed under the determined optimum conditions, linearity was observed between 0.050 and 4.0 mg/L. The detection limit was calculated as 0.017 mg/L as a result of eight repetitive analysis with the lowest concentration of cadmium in the linear region. The efficiency of our method in real samples was determined by recovery studies. As a result of the experiments performed on the tap water samples, the percent recovery values varied between 92 and 117%. These results are quite satisfactory in terms of demonstrating the applicability/accuracy of the method in the real sample.
Keywords: Cadmium; Liquid-liquid microextraction; Tap water; UV-Vis spectrophotometry; MICROEXTRACTION; COPPER; LEAD; CD; PB; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources